Trends in Private Sector Participation in the Indian Water Sector : A Critical Review - World Bank (Washington, DC, 2014)
Public Private Partnerships (PPPs) in the water supply sector began to emerge in the early 1990s in most developing countries of the world. Initiated in most countries by international private operators, these arrangements were typically large-scale PPP projects which required the private operators to finance, develop, operate, and manage the water supply system for a large population base. However, international observers have noted that most of these large-scale projects could not be successfully implemented on account of a host of interrelated factors. These factors included difficulties in achieving financial closure by the private operators, sociopolitical barriers, tariff-setting issues, and high financial risk. The failure of several large-scale projects during this phase resulted in many international private operators withdrawing from such projects in the developing countries. This gave rise to the perception that the number of PPP contracts being pursued in the water supply sector was declining.